Colonialidade, transmodernidade e diferença colonial: para um direito situado na periferia - Rayann Kettuly Massahud de Carvalho (2020)
This dissertation addresses an analysis of law from the decolonial turn. The main objective is to demonstrate that law is an important social category and theoretical category for understanding modernity/coloniality. For this, we map the way in which the decolonial authors understand the law. At first, the writings of Aníbal Quijano are analyzed. In the second moment, the contributions of Enrique Dussel. Finally, Walter Mignolo's work is examined. This current is organized around the Modernity/Coloniality Group and is characterized by the realization of a situated criticism, since its exteriority from modernity. That is, the infinities of cultures, knowledge, memories and stories that were hidden by the supposedly universal Eurocentric modern narrative. Thus, decolonial thinking understands that the beginning of modernity is not about European experiences, but its inaugural moment is the invasion of America. Thus, modernity has a hidden and violent side called coloniality, responsible for disregarding and silencing realities and temporalities that coexist with European modernity. These contributions make it possible to understand the present time and the law in a more appropriate way.